2015
DOI: 10.1002/psc.2766
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and biological properties of Bauhinia bauhinioides kallikrein inhibitor fragments with bradykinin-like activities

Abstract: Proteinase inhibitors extracted form medicinal plants are an interesting source of new drugs. Modifications in the structure of some of this kind of macromolecules could also lead to compounds of interesting biological properties. In this work, we synthesized and tested one fragment containing the reactive site of the Bauhinia bauhinioides kallikrein inhibitor (BbKI), denoted BbKI51-62 , and a related analog (P2 ) in which a proline residue was inserted in order to mimic the N-terminal region of the bradykinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…Conformational studies by Circular Dichroism in different environments were performed (data not shown). The full results of this study is presented elsewhere [5]. Neither BbKI51-62 nor Ri-BbKI51-62 presented bradykinin-like activity, but as expected, the retro-inverso compound was resistant to the enzymes presented in the blood plasma.…”
Section: Resultssupporting
confidence: 58%
“…Conformational studies by Circular Dichroism in different environments were performed (data not shown). The full results of this study is presented elsewhere [5]. Neither BbKI51-62 nor Ri-BbKI51-62 presented bradykinin-like activity, but as expected, the retro-inverso compound was resistant to the enzymes presented in the blood plasma.…”
Section: Resultssupporting
confidence: 58%
“…The peptide was analyzed in pure water and 30, 70 and 100% v/v solutions of 2,2,2 trifluoroethanol (TFE) in water. Fast Fourier Transform (FTF) was used to minimize background effects [141].…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were carried out with C57BL/6J mice from the Centro de Desenvolvimento de Modelos Experimentais da Universidade Federal de São Paulo (CEDEME‐UNIFESP) according to Alves et al . Briefly, the stomach fundus was isolated from the mouse, stripped into two longitudinal muscle strips and mounted into 5‐mL organ baths (Panlab, Cornella, CA, Spain) containing modified Krebs‐Ringer solution: 144 m m NaCl, 5 m m KCl, 1.1 m m MgSO 4 , 25 m m NaHCO 3 , 1.1 m m NaH 2 PO 4 , 1.25 m m CaCl 2 and 5.5 m m glucose at 37 °C (pH 7.4) continuously carboxygenated (95% O 2 /5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%